SISTEM KEAMANAN PENYIMPANAN SURAT PENTING BERBASIS FINGER PRINT - Suhartono, Bambang; Setiawan, Dwi; Masri Masri (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2023)
Administrative work in an institution is inseparable from correspondence. Correspondence documents will then be stored as archives. Storage of important letters requires a storage area with a secure level of security, one of which is using a safety deposit box. The security system is one of the efforts to prevent theft or loss of an object. The security system on conventional storage cabinet doors is prone to file theft because it is easy to break into. Therefore, it is necessary to implement a safe deposit box security system that is safer and has today's technology in order to minimize the occurrence of security deposit box locks being stolen. One way is to use a fingerprint sensor to open a cupboard door, often known as security with a fingerprint. The fingerprint sensor connected to Arduino uno will record the user's registered fingerprint. Through the fingerprint data endroll process. Fingerprint function to open the safe cabinet door, after the finger is pasted on the Finger print sensor. The specialty of this system is that only fingerprints that have been endrolled can open the safe door. Through this system, it can minimize the crime of breaking into storage cabinets. The method used is a prototype so that the design of this system can be developed according to the size of the safe deposit box for important documents